Relationships of diabetes self‐care behaviours to glycaemic control in adults with type 2 diabetes and comorbid heart failure - Fekadu Aga; Sandra B. Dunbar; Tedla Kebede; Melinda Kay Higgins; Rebecca Gary (Wiley, 2020)
Abstract Aim To describe the relationship between diabetes self‐care behaviours and glycaemic control in patients with type 2 diabetes and comorbid heart failure. Design A cross‐sectional, correlational study. Method A secondary analysis of 180 participants' baseline data from a clinical trial that tested a 6‐month integrated self‐care intervention was performed. Correlational and hierarchical linear regression analysis was used to assess the relationships between diabetes self‐care behaviours and glycaemic control. Result The Summary of Diabetes Self‐Care Activities general diet and Summary of Diabetes Self‐Care Activities exercise were negatively associated with glycated haemoglobin (HbA1c), while Summary of Diabetes Self‐Care Activities specific diet was positively associated. Diabetic end‐organ failure, taking insulin only and taking both oral antiglycaemic and insulin, predicted higher HbA1c and fasting blood glucose. African American race and dyslipidaemia predicted higher HbA1c while taking higher total daily medication predicted higher fasting blood glucose. Longer years lived with heart failure, lower ventricular ejection fraction and exposure to chemotherapy predicted lower fasting blood glucose.